Analisis Sentimen Respon Publik Terhadap Program Internet Gratis di Platform X Melalui Pendekatan Algoritma Naïve Bayes - Julianto, Muhammad Rizky; Akbar, Yuma; Wahyudi, Tri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The free internet program was launched in response to the public's need for affordable internet access. Digital transformation relies on four main pillars, including infrastructure, government, digital society, and the economy. In addition, connectivity is also an important component. Indonesia is one of the countries where many people are not connected to the internet. We Are Social reported that there are 63.51 million people throughout the country who have not been connected to the internet until early 2023. The number is the eighth largest globally. After the acceleration of ICT infrastructure development, there is a need for a free internet program initiated by the government or certain organizations that aims to provide wider and more equitable internet access, especially to students and the general public, especially in areas that have not yet received internet access. Although free internet programs are very beneficial, it is undeniable that there are a number of negative impacts that need to be considered. It is important to be aware of and overcome its negative impact. It is necessary to Sentiment Analysis of free internet programs to find out how much positive and negative responses there are in this program with the Naive Bayes algorithm approach so that the need for free internet programs can be realized.